INHIBITION OF OXIDATIVE PHOSPHORYLATION IN ESCHERICHIA COLI BY DIHYDROSTREPTOMYCIN - Bragg, P. D. (1963)
Bragg, P. D. (University of British Columbia, Vancouver, B.C., Canada), and W. J. Polglase. Inhibition of oxidative phosphorylation in Escherichia coli by dihydrostreptomycin. J. Bacteriol. 86:1236–1240. 1963.—Dihydrostreptomycin inhibited the oxidation of succinate in extracts of antibiotic-sensitive Escherichia coli. The inhibitable reaction required both the particulate and the supernatant fractions from sonic extracts which had been centrifuged at 100,000 × g. Dihydrostreptomycin was found to inhibit phosphorylation coupled with the oxidation of reduced nicotinamide adenine dinucleotide (NADH). The inhibition of oxidative phosphorylation by dihydrostreptomycin appeared to precede the effect of the antibiotic on oxidation. The streptomycin antagonist, 2-heptyl-4-hydroxyquinoline N-oxide, inhibited the oxidation of succinate and of NADH, but showed little effect on oxidative phosphorylation. Oxidative phosphorylation was not affected by dihydrostreptomycin in strains of E. coli which were antibiotic-resistant or -dependent.